Growth and magnetic behaviours of La0.7Sr0.3MnO3 nanoparticles synthesized via thermal treatment method - Pan, Kai Yap; Abdul Halim Shaari,; Hussein Baqiah,; Chen, Soo Kien; Jumiah Hassan,; Mohd Mustafa Awang Kechik,; Lim, Kean Pah; Zainal Abidin Talib, (Penerbit Universiti Kebangsaan Malaysia, 2019)
La0.7Sr0.3MnO3 (LSMO) nanoparticles were synthesized by thermal treatment method using water as solvent and polyvinyl pyrollidone (PVP) as capping agent. The as prepared precursor was calcined at various temperatures ranging from 500°C to 1000°C. Structural characterization using X-rays diffractions (XRD) showed that the LSMO nanoparticles, calcined at temperature ≥ 600°C, have single phase of La0.7Sr0.3MnO3 with rhombohedral crystal structure without any secondary phases being detected. The average particle size of nanoparticles increased gradually from 23 to 163 nm for samples calcined at 500 to 1000°C. Magnetic measurement at room temperature using vibrating sample magnetometer (VSM) indicated that the LSMO nanoparticles had soft ferromagnetic behaviour with coercivity ranged from 3.43 to 33.78 G. The magnetic saturation (Ms) of nanoparticles increased with the increment of particle size. From Electron Spin Resonance (ESR) measurement, the g-value of LSMO nanoparticles increased with the increasing of calcination temperature. The ESR indicated a coexistence of ferromagnetic and paramagnetic phases in LSMO nanoparticles below Curie temperature (Tc). The Tc was in the range of 50-80°C for LSMO calcined at 500°C and it is in the range of 80-110°C for LSMO calcined 600, 700, 800, 900, and 1000°C.